2010
DOI: 10.1021/je9009283
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Physicochemical Properties, and Toxicity Data of New Hydrophobic Ionic Liquids Containing Dimethylpyridinium and Trimethylpyridinium Cations

Abstract: O2M3M5MPYR] as the cation and bis(trifluoromethanesulfonyl)imide [NTf 2 ], trifluoromethanesulfonate [TfO], dicyanamide [N(CN) 2 ], thiocyanate [SCN] or iodide as the anion have been synthesized, and their physicochemial properties have been studied. Thermal properties, solubilities in water and water contents, UV-vis spectra, densities, refractive indices, electrochemical windows, and toxicities on Vibrio fischeri have been measured. These ionic liquids, most of which are liquid at room temperature, exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…Heating and cooling cycles were repeated during four cycles to ensure reproducibility (uncertainty was determined to be 0.01 K). Physical-chemical properties of pyrrolidinium ILs have been reviewed by Domańska [61] while new hydrophobic pyridinium-based ILs have been reported by Papaiconomou et al [62] (for some ILs both T g and T m could be determined by DSC, 10 ºC/min rate). A pool of 53 amidinium based potential ILs were synthesised by Dechambenoit et al For some of them the melting point was reported, and it was found that only a few of them qualified as ILs.…”
Section: Measuring Melting Point Of Ionic Liquidsmentioning
confidence: 99%
“…Heating and cooling cycles were repeated during four cycles to ensure reproducibility (uncertainty was determined to be 0.01 K). Physical-chemical properties of pyrrolidinium ILs have been reviewed by Domańska [61] while new hydrophobic pyridinium-based ILs have been reported by Papaiconomou et al [62] (for some ILs both T g and T m could be determined by DSC, 10 ºC/min rate). A pool of 53 amidinium based potential ILs were synthesised by Dechambenoit et al For some of them the melting point was reported, and it was found that only a few of them qualified as ILs.…”
Section: Measuring Melting Point Of Ionic Liquidsmentioning
confidence: 99%
“…13.2) (Zhang et al 2009;Scammells et al 2005). Synthesis method obviously may suffer small variations depending on the type of ILs (Zhang et al 2009;Carrera et al 2010;Ohno and Fukumoto 2007;Pernak et al 2011;Zhao et al 2007;Scammells et al 2005;Harjani et al 2009;Papaiconomou et al 2007Papaiconomou et al , 2010. Commonly the cations are prepared essentially by protonation with a free acid, or by quaternization of an amine or an phosphine.…”
Section: Introduction: a Survey On Il Challengesmentioning
confidence: 99%
“…)-reaction of a Lewis-basic nucleophile heteroatom with an alkyl halide, the mixture being stirred and heated ( Fig. 13.2) (Zhang et al 2009;Pernak et al 2011;Zhao et al 2007;Scammells et al 2005;Harjani et al 2009;Papaiconomou et al 2007Papaiconomou et al , 2010. In the second step, the precursor obtained in the first step is used for anion metathesis with Lewis acids or metal salts of the desired anions finally obtaining a mixture which contain the desired IL ( Fig.…”
Section: Introduction: a Survey On Il Challengesmentioning
confidence: 99%
See 2 more Smart Citations